Faktor Penyebab Rendahnya Jumlah Pria Menjadi Akseptor KB - I Dewa Ayu Ketut Surinati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
The main purpose of this study is to describe factors that causes a low number of men as Family Planning acceptor. The research methods that used in this study is consecutive sampling and for the approach used the cross sectional mode. The results of this study showed that from 123 respondents indeed the presence of factors that cause male respondents did not use family planning in Banjar Karang Suwung. Of all existing factors that cause a low number of men that used family planning, the highest percentage was the knowledge factor which the number of the male respondents that had bad knowledge of family planning are 72 persons (58,55%).